PENGARUH LUAS LAHAN DAN TEKNOLOGI PERTANIAN TERHADAP PRODUKTIVITAS PETANI JERUK DAN SAYUR-MAYUR DI KELURAHAN SARIBUDOLOK - Ramauli Simarmata; Evalina Pakpahan; Simon Patar Rizki Manalu (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
The objective of this study is to analyze the influence of land area and technology on the productivity of citrus and vegetable farmers in Saribudolok Sub-district, Silimakuta District, Simalungun Regency. A quantitative approach was employed using a survey method, by distributing questionnaires to 96 farmer respondents, determined using the Slovin formula. The data were analyzed using SPSS software, which included validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression analysis, partial t-test, simultaneous F-test, and coefficient of determination test. The findings indicate that both land area and agricultural technology have a positive and significant influence on farmer productivity. Among these, agricultural technology has a more dominant effect compared to land area. The coefficient of determination, valued at 51.0%, suggests that these two variables explain more than half of the variation in farmer productivity. The conclusion of this research is that optimizing technology and land access are key factors in enhancing horticultural productivity in highland areas such as Saribudolok. These results offer practical implications for policymakers in designing agricultural programs that are tailored to local needs and efficient in resource utilization.